2009
DOI: 10.1136/bjsm.2009.062547
|View full text |Cite
|
Sign up to set email alerts
|

Does exercise training during pregnancy influence fetal cardiovascular responses to an exercise stimulus? Insights from a randomised, controlled trial

Abstract: In this study, the effects of maternal physical activity level on several fetal haemodynamic parameters such as pulsatility index of the fetal middle cerebral and umbilical arteries and cerebral-to-fetal ratio, as well as on fetal heart rate responses to one bout of moderate exercise (20 min cycle-ergometry at approximately 60% of age-predicted maximum heart rate) during the third pregnancy trimester were assessed. 26 Sedentary and 26 physically active gravidae aged 29 (3) and 30 (2) years, respectively, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
0
17
0
5
Order By: Relevance
“…La escasa variación de la FCF tras el ejercicio materno puede ser considerada como una adaptación fisiológica del corazón fetal a la restricción del flujo uterino que este sufre durante el ejercicio (16,30) y que de nuevo es más eficiente en fetos de madres entrenadas que en las de control.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…La escasa variación de la FCF tras el ejercicio materno puede ser considerada como una adaptación fisiológica del corazón fetal a la restricción del flujo uterino que este sufre durante el ejercicio (16,30) y que de nuevo es más eficiente en fetos de madres entrenadas que en las de control.…”
Section: Discussionunclassified
“…No obstante, a pesar de que son muchos los estudios que se han realizado en busca de respuestas sobre el comportamiento cardiovascular fetal en la gestante que realiza ejercicio, existe aún cierta controversia en cuanto a esa respuesta a diferentes cargas y modalidades de ejercicio materno (12-15) y más aún, no se conoce exactamente cómo influye una carga física regular y programada durante toda la gestación en el comportamiento de la FCF. Todo ello debido posiblemente a la variedad en el diseño de los estudios (16).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Nevertheless, when the focus is the fetus, there are important gaps in the available knowledge, principally with respect to the potential for reduction in uteroplacental flow and its consequences and the decrease in glucose levels. Previous studies have shown a reduction in fetal heart rate (FHR) and an increase in the incidence of bradycardia [8,9], as well as a reduction in glucose levels [10,11], however, results remain contradictory [12,13]. Therefore, with the acute changes that may occur in response to exercise during pregnancy concurrently with the pregnancy effects itself, this study aims to evaluate maternal and fetal responses to acute moderate-intensity exercise, in previously sedentary pregnant women, in two ways: regardless the exercise type and also comparing two physical exercise types (treadmill and stationary bike).…”
Section: Introductionmentioning
confidence: 91%